The Impact of Social Media Communication Forms on Brand Equity Dimensions and Consumer Purchase Intention - Melinda Soewandi (iBuss Management, 2015)
The usage of Internet eventually shifts companies’ marketing strategy from traditional into digital one. Social media, as one of digital marketing tools, can help companies in strengthening their brand. Thus, in this research, the writer want to know the impact of social media communication forms on brand equity dimensions and consumer purchase intention, specifically in Lareia Cake & Co’s Instagram account’s (@lareiacakerie) which is used as this research’s object. There are 250 samples collected using simple random sampling, and Structural Equation Modeling is used to analyze the data. The result of this research implies that both user-generated and firm-created content, as part of social media communication, have positive impact toward brand equity dimensions (brand awareness or brand association, brand loyalty, and perceived quality). In addition, all brand equity dimensions also have positive impact toward consumer purchase intention. However, social media communication forms have negative impact toward consumer purchase intention, when the influence of brand equity dimensions is removed. Keywords: Social Media, Brand Equity, Purchase Intention, Instagram